A Survey: Network Regeneration by Software Defined Network (SDN and SDWN) - Ruya j, Hussein; Iskefiyeli, Murat (International Journal of Computer Sciences and Engineering, 2025)
In the world of information and communication technologies (ICT) ,the up-and-coming trends like (mobile, cloud and big data )are imposing new challenges for coming internet technologies where the high bandwidth ,ever-present accessibility and dynamic management exist .however the dependency of traditional networks on the manual configuration for network devices made it very error prone and hard task to accomplish. Recently one of the most hopeful solutions for future is software defined networks (SDN) which considered important technology for the management of complex and large scale networks which requires re-policing and reconfiguration between whiles. SDN achieves the reconfiguration easily by decoupling the data plane from control plane which enables the network devices (switches/ routers) to easily forward the packets depending on the flow table rules set by control plane .but the implementation of SDN in the wired domain doesn’t mean it will carry the same facility in the wireless domain as a wireless software defined (SDWN) which raises the radio –specific problems in relate to channel estimation and link isolation .